Unexpected multiple sclerosis: follow-up of 30 patients with magnetic resonance imaging and clinical conversion profile. Issue 2 (17th January 2008) - Lebrun, C; Bensa, C; Debouverie, M; De Seze, J; Wiertlievski, S; Brochet, B; Clavelou, P; Brassat, D; Labauge, P; Roullet, E; ,
Abstract : The concept of preclinical multiple sclerosis is now well recognised, and a diagnosis of silent brain T2 lesions is frequent because of the ease of performing MRI. Nevertheless, patients with incidental brain MRI fulfilling Barkhof– Tintoré criteria are more rare. We report a descriptive retrospective study of clinical and 5 year MRI follow-up in patients with subclinical demyelinating lesions fulfilling MRI Barkhof–Tintoré criteria with a normal neurological examination. 30 patients were identified and the first brain MRI was performed for various medical events: headaches (n = 14), migraine with (n = 2) or without (n = 4) aura, craniocerebral trauma (n = 3), depression (n = 3), dysmenorrhoea (n = 2), epilepsy (n = 1) and cognitive changes (n = 1). Mean time for the second brain MRI was 6 months (range 3–30). 23 patients had temporospatial dissemination (eight with gadolinium enhancement). 11 patients had clinical conversion: optic neuritis (n = 5), brainstem (n = 3), sensitive symptoms (n = 2) and cognitive deterioration (n = 1). Eight (72%) already had criteria of dissemination to space and time before the clinical event. Mean time between the first brain MRI and clinically isolated syndrome (CIS) was 2.3 years. To our knowledge, this is the first cohort of CIS with preclinical follow-up. Early treatment should be discussed in view of the predictive value on conversion of the MRI burden of the disease.